MicroRNAs stimulate translation initiation mediated by HCV-like IRESes. Issue 8 (11th January 2017) - Mengardi, Chloé; Limousin, Taran; Ricci, Emiliano P.; Soto-Rifo, Ricardo; Decimo, Didier; Ohlmann, Théophile
Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that control gene expression by recognizing and hybridizing to a specific sequence generally located in the 3΄ untranslated region (UTR) of targeted mRNAs. miRNA-induced inhibition of translation occurs during the initiation step, most probably at the level of ribosome scanning. In this process, the RNA-induced silencing complex interacts both with PABP and the 43S pre-initiation complex to disrupt scanning of the 40S ribosome. However, in some specific cases, miRNAs can stimulate translation. Although the mechanism of miRNA-mediated upregulation is unknown, it appears that the poly(A) tail and the lack of availability of the TNRC6 proteins are amongst major determinants. The genomic RNA of the Hepatitis C Virus is uncapped, non-polyadenylated and harbors a peculiar internal ribosome entry site (IRES) that binds the ribosome directly to the AUG codon. Thus, we have exploited the unique properties of the HCV IRES and other related IRESes (HCV-like) to study how translation initiation can be modulated by miRNAs on these elements. Here, we report that miRNA binding to the 3΄ UTR can stimulate translation of a reporter gene given that its expression is driven by an HCV-like IRES and that it lacks a poly(A) tail at its 3΄ extremity.